Complexity with Heterogeneous Fundamentalists and a Multiplicative Price Mechanism. (3rd August 2014) - Naimzada, Ahmad K.; Ricchiuti, Giorgio
Abstract In contrast with the canonical models of financial markets with heterogeneous agents, , Naimzada and Ricchiuti, (2008, 2009) show that the interaction of groups of agents who have the same trading rule but present different beliefs about the fundamental value could be a source of instability. In this paper, differently from, Naimzada and Ricchiuti, (2008, 2009), we assume that the market maker employs a so‐called multiplicative price mechanism (Tuinstra, 2002; Zhu et al., 2009). We show that the occurrence of heterogeneity has an ambiguous role: it may either stabilize or destabilize the market.